MENINGKATKAN KETEPATAN MELEMPAR BOLA BOCCE DENGAN MEDIA PAPAN PENGARAH PADA ANAK DOWNSINDROM - Rosmiati, Ardisal, Markis Yunus (Universitas Negeri Padang, 2013)
Increasing accuracy using media pitching boccedengan steering board on down syndrome child. In Children Grahita tuna are Class I SDLB Painan This research is motivated by problems that appear in the field two JV kids who are learning Tunagrahita Moderate exercise is still a lot of obstacles. Of the two students who take the sport learning about the game of bocce ball turns out they have not been able to throw the ball bocce bocce court dengna multiply in the tersedia.Penelitian is removed using action research methods class (Classroom Action Research) conducted in collaboration with colleagues. Data was collected through observation techniques, and test, then analyzed qualitatively and kuantitatifHasil research shows that media can help students board directors in directing tosses a bocce ball well this is done through two cycles. There are 4 respectively for the first cycle and for the second cycle that begins with the initial activities, core activities and weekend activities showed good success. Assessment results (preliminary tests) the ability of AR (10%), and WN (10%). In the first cycle, the AR scored average (80%), NW gets the value (100%), and the second cycle using the straight-shaped directional board AR gets average value (100%) and the NW as well (00%) This shows an increase and improvement in success after held a bocce ball toss game. therefore advised to teachers in teaching sports to children Tunagrahita looking better assisted to use tools / media in order to support the expected success rate can be achieved with good, and the children were able to Tunagrahita independently with the accomplishments he achieved through talent and continuous training so as to obtain results that can help them in the future.